2023
DOI: 10.1111/jpr.12485
|View full text |Cite
|
Sign up to set email alerts
|

Achievement Goal Impacts Students' Preferences for “Personalized Problems” in Computer‐Adaptive Tests

Takayuki Goto,
Kei Kano,
Takayuki Shiose

Abstract: The contemporary development of psychometric theories and information technologies enables students to work on algorithm‐based personalized tests in classroom settings. This study aims to investigate the relationship between students' achievement goals and what they prefer as “personalized problems” in computer‐adaptive tests. We theoretically contrast achievement goals with developing competency through mastery and demonstrating competency through performance goals. We asked elementary and secondary school st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…This study is noteworthy for its revelation that future motivation, particularly when intrinsically driven, enhances active learning behaviors beyond the influence of present motivation. Goto et al (2024) examine the interplay between students' achievement goals and their preferences for personalized questions in computer-adaptive tests. The study found that while mastery goals aligned with a preference for challenging problems, performance goals correlated with a preference for successguaranteed problems.…”
mentioning
confidence: 99%
“…This study is noteworthy for its revelation that future motivation, particularly when intrinsically driven, enhances active learning behaviors beyond the influence of present motivation. Goto et al (2024) examine the interplay between students' achievement goals and their preferences for personalized questions in computer-adaptive tests. The study found that while mastery goals aligned with a preference for challenging problems, performance goals correlated with a preference for successguaranteed problems.…”
mentioning
confidence: 99%